KOMPARASI TINGKAT PENDAPATAN USAHATANI KARET RAKYAT DENGAN USAHATANI KELAPA SAWIT RAKYAT DI KABUPATEN BUNGO - Fitri Harahab, Delila (DINAMIKA (Jurnal Manajemen Akutansi Bisnis dan Kewirausahaan), 2020)
The purpose of this study was to analyze the costs and costs obtained by farmers from smallholder rubber farming and smallholder oil palm farming in Pal 16, Pelepat District, Bungo Regency. The results obtained by the daily operational costs in rubber farming is greater when compared to the operational costs of oil palm farming, the cause in the process of collecting rubber latex is done every day using the use of a time spent more labor compared to oil palm farming. Revenues that can be obtained by rubber farmers are between Rp. 21,600,000 / year to 129,600,000 / year, so the income that can be obtained by rubber farmers is between Rp. 19,420,000 / year up to Rp. 127,191,500, - / year. The income of rubber farmers is greater when compared to the income of oil palm farmers. the value of ρ = 0.016 <0.05 and lower value in rubber ushatani> lower in oil palm farming with a difference of 0.0513 or 5%. Thus farmers 'income is 5% higher compared to farmers' income.